2019
DOI: 10.1080/23328940.2019.1614851
|View full text |Cite
|
Sign up to set email alerts
|

Serum from young, sedentary adults who underwent passive heat therapy improves endothelial cell angiogenesis via improved nitric oxide bioavailability

Abstract: Rationale: Passive heat therapy improves vascular endothelial function, likely via enhanced nitric oxide (NO) bioavailability, although the mechanistic stimuli driving these changes are unknown. Objective: To determine the isolated effects of circulating (serum) factors on endothelial cell function, particularly angiogenesis, and NO bioavailability. Methods and Results: Cultured human umbilical vein endothelial cells (HUVECs) were exposed to serum collected from 20 healthy young (22 ± 1 years) adults before (0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 56 publications
3
19
0
Order By: Relevance
“…Therefore, one could imagine that hyperthermia leads to decreased CIRBP expression in the leg, followed by subsequent increases in angiogenesis. Thus far, heat therapy was shown to be of potential benefit to PAD patients by enhancing leg blood flow and improving muscle function [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, one could imagine that hyperthermia leads to decreased CIRBP expression in the leg, followed by subsequent increases in angiogenesis. Thus far, heat therapy was shown to be of potential benefit to PAD patients by enhancing leg blood flow and improving muscle function [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The increase in eNOS content and the consequent angiogenic response to whole-body HT appears to be mediated in part by circulating factors. Brunt and coworkers showed that exposing cultured endothelial cells to serum collected from participants who had undergone whole-body HT for 8 weeks increased the abundance of eNOS and endothelial tubule formation (6). Combined, these studies provide compelling evidence implicating nitric oxide (NO) as a critical mediator of heat-induced skeletal muscle angiogenesis.…”
Section: Effect Of Ht On Muscle Capillarizationmentioning
confidence: 99%
“…following HA in both experimental groups, which can be caused by increased capillary growth (Hesketh et al, 2019) or nitric oxide availability (Brunt et al, 2019) following heat therapy. These changes are consistent with the suggestion that heat therapies elicit changes in skeletal muscle metabolism, the peripheral vasculature or a combination of associated factors (Kim et al, 2020).…”
Section: Discussionmentioning
confidence: 98%